Survival and Control Prognosticators of Recurrent Gynecological Malignancies of the Pelvis and Para-aortic Region Treated with Stereotactic Body Radiation Therapy - Hasan, Shaakir; Ricco, Anthony; Jenkins, Kaylette; Lanciano, Rachelle; Hanlon, Alexandra; Lamond, John; Yang, Jun; Feng, Jing; Good, Michael; Noumoff, Joel; Brady, Luther (Frontiers in Oncology, 2016)
Abstract: Purpose: To define prognostic factors associated with improved survival and local control for gynecologic cancer recurrences limited to the pelvis and para-aortic region using stereotactic body radiation therapy (SBRT). Methods: Between 2/2008 and 7/2014, 30 women (35 targets) with pelvic or PA recurrence of endometrioid (n=12), cervical (n=11), ovarian (n=3), uterine serous (n=2) or carcinosarcoma (n=2) CA were treated with SBRT. Eleven recurrences were located in the central pelvis(CP), 11 along the pelvic sidewall(PSW), and 13 in the para-aortic (PA)region. Results: Five-year survival for all patients was 42% with a median survival of 43.4 months. Multivariate analysis revealed better performance status (PS) and smaller clincial tumor volume (CTV) were significant for improved survival (P<0.05). Local control at 3 years was 90% and 83% for women treated for PSW and PA recurrence compared with 40% for CP recurrence (P=0.02). Patients with cervical CA had no local failures after SBRT, compared to a 3-year LC of 82% for endometroid uterine CA and 33% for ovarian/non-endometroid uterine CA (P=0.02). Multivariate analysis revealed only endometroid uterine and cervical CA and PSW/PA recurrences were significant for improved local control (P<0.05). Conclusion: SBRT is a local therapy for recurrent gynecological malignancies in the pelvis and PA region with curative potential. SBRT is especially effective for LC when targeting PSW or PA recurrence and for patients with a cervical/endometroid uterine primary. Survival is improved for patients with better PS and smaller recurrence volume prior to SBRT.